2012
DOI: 10.1016/j.bbamem.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 hydrophobic segment peptides insertion into membrane mimetic systems: Role of Proline residue

Abstract: Caveolin-1 has a segment of hydrophobic amino acids comprising approximately residues 103-122 that are anchored to the membrane with cholesterol-rich domains. Previously, we reported that changing the Pro(110) residue to Ala (the P110A mutant) prevents not only the localization of the protein into lipid rafts but also the formation and functioning of caveolae. The conformational state of caveolin-1 can be shifted toward the transmembrane arrangement by this single amino acid mutation. To model the conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Further, GUVs can be manipulated after formation to produce highly curved tubules, for example to study the effects of membrane curvature on protein binding (Roux, Cuvelier et al 2005, Tian and Baumgart 2009, Aimon, Callan-Jones et al 2014. Smaller vesicles have been probed by X-ray scattering to determine conformational changes upon membrane binding (Lee, Lee et al 2014), electron microscopy to study membrane tubulation by curvature generating proteins (Shi and Baumgart 2015) or molecular motors (Roux, Cappello et al 2002), and circular dichroism to study the effects of membranes on protein secondary structure (Aoki and Epand 2012). An important technique for evaluation of partitioning in LUVs is Förster Resonance Energy Transfer (FRET), which measures the molecular proximity (interpreted as co-partitioning) between a protein of interest and a wellcharacterized marker for a particular membrane domain (Lin and London 2013).…”
Section: I P O S O M E Smentioning
confidence: 99%
“…Further, GUVs can be manipulated after formation to produce highly curved tubules, for example to study the effects of membrane curvature on protein binding (Roux, Cuvelier et al 2005, Tian and Baumgart 2009, Aimon, Callan-Jones et al 2014. Smaller vesicles have been probed by X-ray scattering to determine conformational changes upon membrane binding (Lee, Lee et al 2014), electron microscopy to study membrane tubulation by curvature generating proteins (Shi and Baumgart 2015) or molecular motors (Roux, Cappello et al 2002), and circular dichroism to study the effects of membranes on protein secondary structure (Aoki and Epand 2012). An important technique for evaluation of partitioning in LUVs is Förster Resonance Energy Transfer (FRET), which measures the molecular proximity (interpreted as co-partitioning) between a protein of interest and a wellcharacterized marker for a particular membrane domain (Lin and London 2013).…”
Section: I P O S O M E Smentioning
confidence: 99%
“…Proline 110 is postulated to be a key residue of the intramembrane turn of caveolin-1 [8, 9, 1113]. Therefore, proline 110 could be essential for the proper fold of Cav1 62–178 , and its mutation to alanine could cause significant changes in the secondary structure of Cav1 62–178 .…”
Section: Resultsmentioning
confidence: 99%
“…However, this postulation was not supported by an in vitro glycosylation study which concluded that P110A had a topology identical to that of the wild-type protein [10]. In contrast, studies using a short, solubility-enhanced construct encompassing residues 103–122, showed significant changes in bilayer depth and α-helicity when the P110A mutation was made [11]. …”
Section: Introductionmentioning
confidence: 99%
“…In a study which compared the solvent accessibility of wild-type and P110A IMD constructs (residues 102e122) using fluorescence quenching and l max determinations, it was found that the overall tryptophan environment appeared to differ between constructs (with the P110A mutant becoming less solvent accessible), consistent with a topological change for the mutant (Aoki & Epand, 2012). Additionally, circular dichroism spectroscopy was used to compare the secondary structure of the wild-type and mutant and showed an increase in the a-helical character on the order of 1.5-to 2-fold in the case of the mutant, consistent with the reported linearization of the protein upon P110A mutation.…”
Section: Proline 110 May Be Critical To the Native Caveolin-1 Topologymentioning
confidence: 85%